2015
DOI: 10.4103/0255-0857.150919
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular epidemiology of methicillin resistant staphylococcus aureus colonizing the anterior Nares of school children of Udupi Taluk

Abstract: The Indian variant EMRSA-15 gains much epidemiological relevance owing to the acquisition of pvl gene. In spite of low prevalence of nasal colonization of MRSA, emergence of the virulent Indian variant EMRSA-15 in our community is a worrisome fact to be reckoned with.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…Another very similar project to ours was conducted in Argentina, where 316 healthy children were screened in a given city, and here again all 14 MRSA strains carried the SCCmec type IV cassette [26]. On the other hand, in India, where 1,503 school-age children were screened, only 7 out of the 17 MRSAs belonged to type IV and none were identified as type V either [27]. The MLST typing revealed that all MRSA isolates in this study belonged to ST45, a clone which has been very frequently reported from numerous countries from all over the world, based on the MLST database [9].…”
Section: Discussionsupporting
confidence: 61%
“…Another very similar project to ours was conducted in Argentina, where 316 healthy children were screened in a given city, and here again all 14 MRSA strains carried the SCCmec type IV cassette [26]. On the other hand, in India, where 1,503 school-age children were screened, only 7 out of the 17 MRSAs belonged to type IV and none were identified as type V either [27]. The MLST typing revealed that all MRSA isolates in this study belonged to ST45, a clone which has been very frequently reported from numerous countries from all over the world, based on the MLST database [9].…”
Section: Discussionsupporting
confidence: 61%
“…The carriage of pvl gene (pvl+) in 44.7% of MRSA isolates in this report is consistent with 58.8% reported by Govindan et al (37) and in dissidence with reports from Nigeria (16%) (38), Egypt (2.2%) (39), Uganda (73%) (40). In our study, among the tested mecA+ MRSA isolates, pvl+ was chiefly associated with HA genotype (37.5%).…”
Section: Discussionsupporting
confidence: 91%
“…A soothing fact to be noted is the absence of such multi-drug resistant MRSA in their study settings. This indicates that neither HA-MRSA has invaded into community settings nor CA-MRSA has acquired multi-drug resistance genes ( 27 ).…”
Section: Discussionmentioning
confidence: 99%